Lorca and homosexual love in the Spanish cinema of the Transition: To an unknown god (Chávarri, 1977): - Serrano Martín, Carlos (Estudios LGBTIQ+, Comunicación y Cultura, 2024)
This paper, with the help of AI, qualitatively analyses the footage of the Spanish film A un dios desconocido (Chávarri, 1977). The reason for choosing this audiovisual work responds to the following criterion: the footage aims to recover the figure of García Lorca, a leading author of 20th century Spanish literature and a prominent and repressed figure of the LGTBIQ+ community by the Franco dictatorship. Furthermore, its year of release takes place in a key context of contemporary history: the Spanish Transition. The film stands out for its footage that presents the viewer with a defence of free love and tolerance.
Keywords: Homosexuality; Spanish Transition; Film analysis; Artificial Intelligence